A sociocognitive approach to social norms - Dubois, Nicole (Routledge research international series in social psychology., 2003)
Societies and groups attribute greater value to some behaviours and some judgments. These 'norms' are what is most important for understanding how behaviours and judgments are socially regulated. The approach presented examines in particular the social foundations of our judgments.